2022
DOI: 10.3390/molecules27051677
|View full text |Cite
|
Sign up to set email alerts
|

Resolvins, Protectins, and Maresins: DHA-Derived Specialized Pro-Resolving Mediators, Biosynthetic Pathways, Synthetic Approaches, and Their Role in Inflammation

Abstract: Marine organisms are an important source of natural products with unique and diverse chemical structures that may hold the key for the development of novel drugs. Docosahexaenoic acid (DHA) is an omega-3 fatty acid marine natural product playing a crucial regulatory role in the resolution of inflammation and acting as a precursor for the biosynthesis of the anti-inflammatory specialized pro-resolving mediators (SPMs) resolvins, protectins, and maresins. These metabolites exert many beneficial actions including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 126 publications
0
26
0
Order By: Relevance
“…The relative proportions of individual PUFA can also modulate cell function by influencing the pattern of lipid second messengers produced in response to stimulation including oxylipins such as eicosanoids and leukotrienes (Wada et al, 2007), and phospholipid‐derived mediators, for example diacylglycerol (Kamiya et al, 2016) and phosphatidic acid (Heung & Postle, 1995a, 1995b). EPA and DHA are substrates for synthesis of specialized pro‐resolving mediators that are important for immune homeostasis (Calder, 2017; Ferreira et al, 2022). Moreover, ω‐3 PUFA can influence transcription by acting as ligands for transcription factors, for example the peroxisome proliferator‐activated receptor (PPAR) family (Forman et al, 1997), and by modifying epigenetic processes (Burdge & Lillycrop, 2014; Perez‐Mojica et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions of individual PUFA can also modulate cell function by influencing the pattern of lipid second messengers produced in response to stimulation including oxylipins such as eicosanoids and leukotrienes (Wada et al, 2007), and phospholipid‐derived mediators, for example diacylglycerol (Kamiya et al, 2016) and phosphatidic acid (Heung & Postle, 1995a, 1995b). EPA and DHA are substrates for synthesis of specialized pro‐resolving mediators that are important for immune homeostasis (Calder, 2017; Ferreira et al, 2022). Moreover, ω‐3 PUFA can influence transcription by acting as ligands for transcription factors, for example the peroxisome proliferator‐activated receptor (PPAR) family (Forman et al, 1997), and by modifying epigenetic processes (Burdge & Lillycrop, 2014; Perez‐Mojica et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of propargyl bromide intermediate 4 is detailed in Scheme 3. This synthesis employed D-erythrose (9) as a chiral feedstock. However, in our recent and separate study 8 postdating the current synthesis, we found D-erythronolactone as a more suitable chiral synthon than 9 due to its high cost and handling difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-inflammatory properties of n-3 LC-PUFAs have been known for a long time, and are thought to occur (i) by the replacement of ARA by DHA in cellular membranes, lowering the production of pro-inflammatory eicosanoids from ARA by COX and lipoxygenase; (ii) the fact that DHA is preferred to ARA as a substrate of COX-2 enzyme; and (iii) by the synthesis of lipidic specialized pro-resolving mediators (SPMs), namely, resolvins, protectins, and maresins, which are enzymatically oxygenated PUFAs (or oxylipins) acting as lipid mediators to suppress inflammation by clearing neutrophils and macrophages from inflammatory sites [82][83][84][85][86] (Figure 3). However, the synthesis of SPMs in humans is not clearly linked to n-3 LC-PUFA dietary supplementation [87].…”
Section: Anti-inflammatory Effect Of N-3 Lc-pufas and Cancer Preventionmentioning
confidence: 99%